2017
DOI: 10.1080/21695717.2017.1325094
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems among 4–17-year-olds with hearing problems

Abstract: Objective: This study aimed to characterise the risk of mental health problems among a representative sample of 6,310 4-17 year olds, 147 of whom had parent-reported hearing problems. Methods:The study used data from the Young Minds Matter survey. The Diagnostic Interview Schedule for Children (DISC-IV) assessed prevalence of mood, anxiety and behavioural disorders. The Strengths and Difficulties Questionnaire (SDQ) assessed social and emotional problems. Logistic regression models were used to estimate odds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Regarding types of bullying, the current study found that verbal and social bullying were reported in more than two thirds of males and in nearly two thirds of females deaf and dump students. These results supported by most studies that find verbal and social bullying occurs most often, followed by physical bullying U.S. Department of Health and Human Services, 2018, Kowalski et al, 2012, Olweus, 2013 and Salmivalli et al, 2013 (9,32,33,34) Moreover, the current study found that physical bullying was reported in less than half of males and more than quarter of females deaf and dump students.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding types of bullying, the current study found that verbal and social bullying were reported in more than two thirds of males and in nearly two thirds of females deaf and dump students. These results supported by most studies that find verbal and social bullying occurs most often, followed by physical bullying U.S. Department of Health and Human Services, 2018, Kowalski et al, 2012, Olweus, 2013 and Salmivalli et al, 2013 (9,32,33,34) Moreover, the current study found that physical bullying was reported in less than half of males and more than quarter of females deaf and dump students.…”
Section: Discussionsupporting
confidence: 87%
“…Of note, Hancock et al found that DHH children had higher rates of anxiety and behavioral disorders than hearing peers, independent of bullying experiences. 20…”
Section: Health Consequences Of Bullying For Dhh Childrenmentioning
confidence: 99%
“…Several studies have described the close relationship between hearing loss and motor development, suggesting that DHH children were at higher risk of deficits in balance and fine motor skills, with 12% of young DHH children detected with early gross motor developmental delay and one fifth of school age DHH children to be less competent in gross and fine motor skills compared to typical hearing peers ( 9 , 11 , 42 ). Children with slight/mild HL have also been reported to have significantly poorer physical HRQoL compared to typical hearing children ( 33 ) hypothesized to be related to inner ear abnormalities or the lack of environmental exposure due to sensory deprivation. Concurrent gross motor delay among DHH children is likely to intensify emotional/behavioral difficulties as the presence of motor delay in typical hearing children have been reported to have more emotional/behavior difficulties ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though emotional/ behavioral mean scores were within normal range, the wide standard deviations and high proportion of scores indicative of Our study demonstrated a high prevalence of hyperactivity symptoms among both groups of DHH children. Although a review study reported contradicting results (2), many earlier studies have demonstrated ADHD-like symptoms among DHH children (6,33). Hyperactivity symptoms are not unexpected, as children with HL and ADHD share similar difficulties in executive function and self-regulation (34,35).…”
Section: Outcomes Of Unilateral/mild Hearing Lossmentioning
confidence: 99%